Operating Room Scheduling with Respect to Dynamic Facilities and Surgeon Specialty - Seyyed Jamaloddin Hosseini; Jalal Rezaeenoor; Amir Hosein Akbari; Mohammad Reza Marjani (مدیریت صنعتی, 2021)
Objective: Hospitals are one of the most important elements of the health sector, which is the most important and costly part of them are operating rooms. Therefore, locating and allocating resources appropriately and appropriate scheduling for the operating room, can greatly solve the health problems of the community. In this article, an integrated model for locating-allocating and scheduling the operating rooms to build facilities at the appropriate places, allocating patients to facilities and operating rooms and scheduling operating rooms with the goals of reducing costs and reducing the overtime of the operating rooms, is presented. Also, surgeons have the maximum working time per day, and then their performance is faced with an error. Methods: Given the NP-hard of the model and the inability of accurate methods for solving large-scale problems, a metaheuristic method based on the genetic algorithm has been developed for the problem and its efficiency has been studied in a wide range of samples examples. Results: Computational results showed that the proposed algorithms can effectively help to generate reasonable responses. Conclusion: The results of the problem indicate the importance of locating and integrating scheduling of facilities in reducing the waiting time of patients and their distance from facilities. The proposed algorithm is also capable of solving large-scale problems at an efficient response.